Communication media and linguistic concreteness: evidence from firm site visits in China - Songlian Tang; Jiangnan Geng (China Journal of Accounting Research)
The digital transformation of communication media has been widely adopted and has reshaped institutional investor interactions. We examine how the linguistic concreteness of investors’ questions adapts to online media and face-to-face communication, using textual analysis of investor–company Q&A transcripts from Chinese listed firms. We find that online media environments induce investors to enhance linguistic precision, to compensate for reduced nonverbal cues and social presence. This mechanism is moderated by sender characteristics, message attributes and response concreteness patterns. Such adjustments counteract media-induced information loss, evidenced by improved analyst forecast accuracy. Our study represents a practical application of Lasswell’s “5W” communication model in the context of corporate information disclosure and expands research on the impact of digital technology on communication media, offering insights into the balance between sender intent and media characteristics.